PENGARUH DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA MEKARSARI CAKE & BAKERY SUKARESIK KABUPATEN TASIKMALAYA - Ridwan Hakiki (Journal of Innovation Research and Knowledge, 2023)
The problem in this study, is related to the work productivity of employees contained in Mekarsari Cake & Bakery which is influenced by work discipline. This study aims to determine: 1. How is the work discipline in Mekarsari Cake & Bakery Sukaresik, Tasikmalaya Regency; 2. How is Employee Productivity in Mekarsari Cake & Bakery Sukaresik, Tasikmalaya Regency; 3. How is the influence of work discipline to employee productivity in Mekarsari Cake & Bakery Sukaresik, Tasikmalaya Regency. The method used in this research is descriptive quantitative with the nature of the research in the form of a replica. This study uses primary data by distributing questionnaires as measured by a likert scale research instrument. The sample in this study amounted to 30 people, namely all employees of Mekarsari Cake & Bakery Sukaresik, Tasikmalaya Regency. The analytical tool used is simple regression analysis. The results of this study indicate that: 1) Work discipline in Mekarsari Cake & Bakery Sukaresik, Tasikmalaya Regency is considered good 2) The work productivity of employees in Mekarsari Cake & Bakery Sukaresik, Tasikmalaya Regency is considered good 3) Based on the results of simple linear regression analysis calculations regarding the effect of work discipline to employee work productivity, the sign is positive and has significant influence.